Ruthenium nano-cluster / trinickel disulfide heterojunction composite material as well as preparation method and application thereof

By growing Ni3S2 nanosheet arrays in situ on a foam nickel substrate and anchoring the ruthenium nanoclusters to form a ruthenium nanocluster/trini nickel disulfide heterojunction composite, the problems of insufficient catalyst activity and complex preparation methods are solved, and efficient and stable electrolytic water catalysis is achieved, which is suitable for large-scale production.

CN119571381APending Publication Date: 2025-03-07SUZHOU UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411772148.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, the catalyst has insufficient catalytic activity during the electrolytic hydrogen production process, the preparation method is complicated and not suitable for large-scale production, and the catalyst may fall off during long-term reactions, resulting in stability problems.

Method used

The ruthenium nanocluster/trini nickel disulfide heterojunction composite was formed by growing the Ni3S2 nanosheet array in situ on a foamed nickel substrate and anchoring the ruthenium nanoclusters by chemical etching. This method is simple and low-cost, suitable for large-scale production, and increases the specific surface area of ​​the catalyst through a honeycomb structure.

Benefits of technology

It achieves high catalytic activity and reduces overpotentiality of the catalyst, is suitable for large-scale production, and has excellent stability in long-term reactions. It is suitable for hydrogen evolution and oxygen evolution catalysis of electrolytic water reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571381A_ABST
    Figure CN119571381A_ABST
Patent Text Reader

Abstract

The invention relates to a ruthenium nano-cluster / trinickel disulfide heterojunction composite material as well as a preparation method and application thereof. According to the composite material, foamed nickel serves as a substrate material, a Ni3S2 nanosheet array grows on the surface of the substrate material in situ, and ruthenium nanoclusters are anchored on the surface of the Ni3S2 nanosheet array to form the heterojunction composite material. According to the preparation method, the Ni3S2 nanosheet array grows on the foamed nickel substrate in situ, then the composite material with the ruthenium nanocluster anchored on the Ni3S2 surface is prepared through a chemical etching method, and the preparation method is simple, relatively low in cost and suitable for large-scale production; the prepared heterojunction composite material forms a nanosheet array structure and shows a honeycomb structure, so that the catalyst has a relatively large specific surface area, provides more active sites for catalytic reaction, is high in catalytic activity, and can be used as a catalyst applied to hydrogen evolution and oxygen evolution of water electrolysis reaction in electro-catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a ruthenium nanocluster / nickel disulfide heterojunction composite material and a preparation method and application thereof. Background Art

[0002] Hydrogen is known as the most promising energy carrier. It has the advantages of being clean, efficient, and widely available. Therefore, it is expected to solve the current crisis of increasing depletion of fossil fuels and deteriorating ecological environment. Hydrogen production by water electrolysis can make the thermodynamically non-spontaneous water electrolysis reaction occur under the impetus of electrical energy, expanding the research field of hydrogen production methods. At the same time, hydrogen production by water electrolysis can effectively utilize renewable solar energy and wind energy, and realize carbon-free, energy-saving, and green hydrogen production through solar power generation or wind power generation.

[0003] The electrolysis reaction of water includes the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode, wherein the slow reaction kinetics of the HER and OER processes severely limit the efficiency of the electrolysis of water. The complex electron transfer and slow kinetics during the electrolysis of water lead to a large amount of energy consumption, so the actual applied voltage often needs to be greater than the theoretical voltage value of the electrolysis of water, which brings about the problem of energy consumption. The existing technology generally uses effective catalysts to reduce the overpotential of the HER and OER reactions to improve the efficiency of hydrogen production by electrolysis of water and reduce the energy consumption of the reaction. At present, Pt, Ir, and Ru-based precious metal catalysts are recognized as the most effective catalysts in the field of electrolysis of water. However, the scarcity of precious metals and their high prices make them unsuitable for industrialization and commercialization. Ni belongs to the same main group as Pt, and its structure has certain similarities with the highly catalytically active Pt. Therefore, Ni-based materials are considered to be a type of catalyst with research prospects. On the other hand, transition metal sulfides have attracted widespread attention due to their good conductivity, abundant element reserves and low cost. Nickel-based sulfides, especially Ni 3 S 2 , which is considered to be a promising Ni-based catalyst due to its high activity.

[0004] Although its activity has been improved compared to other non-precious metal catalysts, it still has shortcomings compared to traditional precious metal catalysts. How to effectively improve the catalytic activity of this type of material is still an urgent problem that needs to be solved; in addition, many preparation methods with complex processes not only consume huge amounts of energy, but also have stringent requirements on experimental conditions, making them unsuitable for large-scale production, and therefore have no commercial and industrial prospects; in addition, in the process of industrial electrolysis of water to produce hydrogen, the catalyst may fall off during a long reaction process, so improving the stability of the catalyst is also one of the problems that need to be solved. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a ruthenium nanocluster / nickel disulfide heterojunction composite material and its preparation method and application. The present invention in situ grows Ni on a nickel foam substrate. 3 S 2 The Ni nanosheet array was then prepared by chemical etching. 3 S 2 The composite material of surface-anchored ruthenium nanoclusters has a simple preparation method and relatively low cost, and is suitable for large-scale production. The prepared heterojunction composite material forms a nanosheet array structure and exhibits a honeycomb structure, which gives the catalyst a larger specific surface area, provides more active sites for the occurrence of catalytic reactions, and has high catalytic activity. It can be used as a catalyst for hydrogen evolution and oxygen evolution in electrocatalytic water electrolysis reactions.

[0006] The Ru nanocluster / nickel disulfide heterojunction composite material prepared by the present invention can be used as an electrocatalyst to electrocatalyze the decomposition of water molecules to produce hydrogen and oxygen at room temperature, and when used as a hydrogen evolution and oxygen evolution electrocatalyst respectively, the current density is 100 mA cm -2 The overpotentials at 54 mV and 216 mV were 50 mA cm-1 and 50 mA cm-2, respectively. -2 The voltage is only 1.62V, and it has excellent full water electrolysis stability. This heterojunction composite material has good application prospects in water electrolysis and hydrogen production.

[0007] The first object of the present invention is to provide a ruthenium nanocluster / nickel disulfide heterojunction composite material, wherein the composite material uses nickel foam as a base material, and the surface of the base material in situ grows Ni 3 S 2 Nanosheet arrays, the Ni 3 S 2 Ruthenium nanoclusters are anchored on the surface of nanosheet arrays to form heterojunction composite materials.

[0008] In some embodiments of the present invention, the ruthenium nanocluster / nickel disulfide heterojunction composite material is a honeycomb structure.

[0009] In some embodiments of the present invention, the loading amount of the ruthenium nanoclusters is less than or equal to 427.6 μg cm -2 .

[0010] The second object of the present invention is to provide a method for preparing a ruthenium nanocluster / nickel disulfide heterojunction composite material, comprising the following steps:

[0011] S1. Provide a nickel foam;

[0012] S2, immersing the nickel foam in a mixed solvent, adding a nickel source and a sulfur source and mixing them, and performing a solvent thermal reaction to obtain a nickel foam-loaded Ni 3 S 2 Ultrathin nanosheet arrays;

[0013] S3, the Ni foam loaded with nickel obtained in step S2 3 S 2 The ultra-thin nanosheet array is added into a ruthenium source solution and reacted at a constant temperature to obtain the ruthenium nanocluster / nickel disulfide heterojunction composite material.

[0014] In some embodiments of the present invention, in step S2, the nickel source is selected from Ni(NO 3 ) 2 、NiSO 4 and Ni(CH 3 COO 2 One or more of;

[0015] The concentration of the nickel source is 0.01-0.05 mmol / mL;

[0016] The mixed solvent includes ethanol and N,N-dimethylacetamide;

[0017] The volume ratio of the ethanol to N,N-dimethylacetamide is (1:1)-(4:1).

[0018] In some embodiments of the present invention, in step S2, the molar ratio of the sulfur source to the nickel source is (1:1)-(3:1);

[0019] The sulfur source is selected from one or more of thioacetamide, thiourea, L-cysteine ​​and sulfur powder;

[0020] The conditions of the solvent thermal reaction are as follows: the reaction temperature is 120-180° C. and the reaction time is 3-8 h.

[0021] In some embodiments of the present invention, in step S3, the ruthenium source in the ruthenium source solution is selected from RuCl 3 and / or terpyridinium ruthenium chloride hexahydrate;

[0022] The concentration of the ruthenium source is 0.2-4 mg / mL;

[0023] The solvent of the ruthenium source is selected from ethanol and / or deionized water;

[0024] The temperature of the isothermal reaction is 60-100° C., and the isothermal time is 6-18 hours.

[0025] The third object of the present invention is to provide an oxygen evolution electrode, comprising the ruthenium nanocluster / nickel disulfide heterojunction composite material.

[0026] The fourth object of the present invention is to provide a hydrogen evolution electrode, comprising the ruthenium nanocluster / nickel disulfide heterojunction composite material.

[0027] A fifth object of the present invention is to provide an electrochemical device for water electrolysis reaction, comprising the oxygen evolution electrode or the hydrogen evolution electrode.

[0028] The above technical solution of the present invention has the following advantages compared with the prior art:

[0029] (1) The present invention uses a simple experimental method to anchor a small amount of Ru nanoclusters on Ni 3 S 2 The surface of the nanosheets, the experimental method is simple and can realize the large-scale production of catalysts. 3 S 2 The formed honeycomb-like nanosheet array provides more sites for the attachment of Ru, thus Ru nanoclusters and Ni 3 S 2 A large number of heterogeneous interfaces are formed, and the formation of heterogeneous interfaces provides more active sites for the occurrence of water electrolysis reaction.

[0030] (2) In the present invention, Ni 3 S 2 The introduction of a very small amount of Ru into the catalyst significantly improved the catalytic performance of hydrogen and oxygen evolution, making the prepared Ru-Ni 3 S 2 The hydrogen and oxygen evolution performance of @NF is good at a current density of 100 mA cm -2 The overpotentials at 200 MHz and 500 MHz were only 54 mV and 216 mV, respectively, which far exceeds the catalytic performance of metal sulfides reported in recent years. They were assembled into a two-electrode water electrolysis system, which exhibited excellent electrochemical properties at a current density of 50 mA cm -2 The voltage is only 1.62V, which is much lower than the voltage of transition metal sulfides reported in recent years, so its full electrolytic water catalytic performance is excellent. Therefore, the present invention provides a solution for preparing electrolytic water catalysts with high catalytic performance, which is expected to promote scientific and technological progress and industrial development in related fields.

[0031] (3) Prepared Ru-Ni 3 S 2 @NF can not only realize hydrogen and oxygen evolution reactions at high current density, but also exhibit excellent durability when the current density is relatively large, and can thus achieve long-term operation at high current density. It is expected to be industrially applied as a catalyst for alkaline water electrolysis tanks. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0033] Figure 1 The Ru-Ni obtained in Example 1 of the present invention 3 S 2 @NF and Ni 3 S 2 XRD and Ru-Ni of @NF 3 S 2 @NF SEM; where a is the XRD pattern and b is the SEM pattern.

[0034] Figure 2 The Ru-Ni obtained in Example 1 of the present invention 3 S 2 @NF, Ni 3 S 2 Hydrogen evolution performance of nickel foam (Pt / C@NF), commercial Pt / C supported on nickel foam (Pt / C@NF), and clean nickel foam (NF); where a is the polarization curve of hydrogen evolution and b is the voltage required for different catalysts at the same current density.

[0035] Figure 3 The Ru-Ni obtained in Example 1 of the present invention 3 S 2 @NF and Ni 3 S 2 @NF、RuO 2 @NF oxygen evolution catalytic performance; where a is the polarization curve of oxygen evolution, and b is the overpotential required for different catalysts at the same current density.

[0036] Figure 4 The full electrolysis water performance test results of the composite material obtained in Example 1 of the present invention; wherein a is a schematic diagram of full electrolysis water, and b is a polarization curve of full electrolysis water.

[0037] Figure 5 The composite material Ru-Ni obtained in Example 1 of the present invention 3 S 2 @NF full electrolysis water stability test; where a is the current density of 50mA cm -2 a is the voltage-time curve of 4000 CV cycles, b is the polarization curve of full water electrolysis before and after 4000 CV cycles. DETAILED DESCRIPTION

[0038] In order to solve the technical problems pointed out in the background technology, the present invention achieves the purpose of the present invention through the following scheme:

[0039] The present invention provides a ruthenium nanocluster / nickel disulfide heterojunction composite material, wherein the composite material uses nickel foam as a base material, and Ni is in situ grown on the surface of the base material. 3 S 2 Nanosheet arrays, the Ni 3 S 2 Ruthenium nanoclusters are anchored on the surface of nanosheet arrays to form heterojunction composite materials.

[0040] In a specific embodiment of the present invention, the ruthenium nanocluster / nickel disulfide heterojunction composite material is a honeycomb structure.

[0041] In a specific embodiment of the present invention, the loading amount of the ruthenium nanoclusters is less than or equal to 427.6 μg cm -2 The present invention is achieved by 3 S 2 The surface of the Ru nanoclusters forms a honeycomb-like nanosheet array, which provides more sites for the attachment of Ru nanoclusters. 3 S 2 A large number of heterogeneous interfaces are formed, and the formation of heterogeneous interfaces provides more active sites for the occurrence of water electrolysis reaction.

[0042] The present invention also provides a method for preparing a ruthenium nanocluster / nickel disulfide heterojunction composite material, comprising the following steps:

[0043] S1. Provide a nickel foam;

[0044] S2, immersing the nickel foam in a mixed solvent, adding a nickel source and a sulfur source and mixing, and performing a hydrothermal reaction to obtain a nickel foam-loaded Ni 3 S 2 Ultrathin nanosheet arrays;

[0045] S3, the Ni foam loaded with nickel obtained in step S2 3 S 2 The ultra-thin nanosheet array is added into a ruthenium source solution and reacted at a constant temperature to obtain the ruthenium nanocluster / nickel disulfide heterojunction composite material.

[0046] In a specific embodiment of the present invention, in step S2, the nickel source is selected from Ni(NO 3 ) 2 、NiSO 4 and Ni(CH 3 COO 2 One or more of; further, preferably Ni(NO 3 ) 2 .

[0047] The concentration of the nickel source is 0.01-0.05 mmol / mL, and illustratively, it can be 0.01 mmol / mL, 0.02 mmol / mL, 0.03 mmol / mL, 0.04 mmol / mL, 0.05 mmol / mL, or any interval value between any two values;

[0048] The mixed solvent includes ethanol and N,N-dimethylacetamide;

[0049] The volume ratio of the ethanol to N,N-dimethylacetamide is (1:1)-(4:1).

[0050] In a specific embodiment of the present invention, in step S2, the molar ratio of the sulfur source to the nickel source is (1:1)-(3:1);

[0051] The sulfur source is selected from one or more of thioacetamide, thiourea, L-cysteine ​​and sulfur powder;

[0052] The conditions of the solvent thermal reaction are as follows: the reaction temperature is 120-180°C, and illustratively, it can be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, or any interval between any two values; the reaction time is 3-8h, and illustratively, it can be 3h, 4h, 5h, 6h, 7h, 8h; or any interval between any two values.

[0053] In a specific embodiment of the present invention, in step S3, the ruthenium source in the ruthenium source solution is selected from RuCl 3 and / or terpyridyl ruthenium chloride hexahydrate; further, preferably RuCl 3 .

[0054] The concentration of the ruthenium source is 0.2-4 mg / mL, and illustratively, it can be 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 1 mg / mL, 1.5, 2.0, 2.5, 3.0, 3.5, 4, etc., or any interval value between any two values;

[0055] The solvent of the ruthenium source is selected from ethanol and / or deionized water;

[0056] The temperature of the isothermal reaction is 80° C., and the isothermal time is 12 hours.

[0057] The present invention also provides an oxygen evolution electrode, comprising the ruthenium nanocluster / nickel disulfide heterojunction composite material.

[0058] The present invention also provides a hydrogen evolution electrode, comprising the ruthenium nanocluster / nickel disulfide heterojunction composite material.

[0059] The present invention also provides an electrochemical device for water electrolysis reaction, comprising the oxygen evolution electrode or the hydrogen evolution electrode.

[0060] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0061] Example 1

[0062] This embodiment provides a method for preparing a heterogeneous composite electrode material, comprising the following steps:

[0063] 1. Preparation of Materials

[0064] (1) First, the sheet-like nickel foam is ultrasonically cleaned with an acetone solution for 10 minutes to clean the organic matter and other impurities on its surface; then, it is washed with water, and then ultrasonically cleaned with a 1 mol / L hydrochloric acid solution for 10 minutes to clean the metal oxide and other impurities on its surface, and finally, it is rinsed with clean water for later use;

[0065] (2) Using a solvothermal method, Ni 3 S 2 Ultrathin nanosheet array: 28 mL of ethanol and N,N-dimethylacetamide were mixed in a volume ratio of 5:2, and 1 mmol of Ni(NO 3 ) 2 6H 2 O and 100 mg of thioacetamide are dissolved in the mixed solution, and stirred at room temperature for 30 min. The obtained solution is then transferred to a reactor, and the cleaned nickel foam in step (1) is placed in the reactor. Finally, the reactor is sealed and transferred to a constant temperature box, and kept at a temperature of 150° C. for 5 h. After naturally cooling to room temperature, it is taken out, rinsed with water, placed in a vacuum drying oven, and dried at 60° C. for 12 h to obtain nickel foam-loaded Ni. 3 S 2 Ultrathin nanosheet arrays (Ni 3 S 2 @NF).

[0066] (3) The Ni prepared in step (2) 3 S 2 @NF immersed in 1mg / mL RuCl 3 The Ru nanocluster-anchored Ni 3 S 2 Nanosheet composites (Ru-Ni3 S 2 @NF).

[0067] 2. The prepared materials were characterized by SEM and XRD, and the characterization results are as follows:

[0068] Figure 1 Figure a shows the Ni prepared in this example. 3 S 2 @NF and Ru-Ni 3 S 2 @NF XRD, as shown in the figure, the diffraction peaks at 21.7°, 31.1°, 37.8°, 49.7°, and 55.2° correspond to Ni 3 S 2 The (101), (110), (003), (113) and (122) crystal planes of the RuO2O3 are shown in Table 1. The diffraction peaks at 44.5°, 51.8° and 76.4° are from the substrate nickel foam. 3+ There is no obvious change in XRD before and after etching, that is, no diffraction peak of Ru oxide or Ru sulfide appears, which can be attributed to the loading on Ni 3 S 2 The amount of Ru on the surface is low, and the ICP test found that the Ru loading was as low as 427.6 μg cm -2 .

[0069] like Figure 1 As shown in Figure b, a large number of ultrathin nanosheet arrays are formed on the surface of the nickel foam, and the nanosheets form a honeycomb-like structure, which is not only beneficial to the mass transfer during the reaction but also helps to expose the active sites, thus facilitating the occurrence of the reaction.

[0070] 3. Performance Study

[0071] 1. Hydrogen evolution performance test

[0072] (1) The electrocatalytic performance tests of hydrogen and oxygen evolution were carried out using a three-electrode system on a Shanghai Chenhua electrochemical workstation (CHI660e). 3 S 2 @NF and other control samples, mercury oxide, and carbon rod were used as working electrode, reference electrode, and counter electrode, and 1 M KOH was used as electrolyte;

[0073] (2) Linear voltammetry (LSV) was used to preliminarily evaluate the hydrogen evolution performance of the synthesized catalyst. Figure 2 As shown in Figure a, Ni without chemical etching 3 S 2@NF, commercial Pt / C loaded with nickel foam (Pt / C@NF) and clean nickel foam (NF) were used as control samples. From their polarization curves, it can be seen that in Ni 3 S 2 After Ru nanoclusters are formed on the surface of the catalyst, its hydrogen evolution performance is greatly improved, and its hydrogen evolution catalytic performance exceeds that of commercial Pt / C at relatively high voltages. Figure 2 Figure b shows that the current density reaches 50 mA cm -2 、300mAcm -2 、600mAcm -2 The overpotential is relatively low.

[0074] 2. Oxygen evolution performance test

[0075] (1) The three-electrode system was also used to test Ru-Ni in 1M KOH solution. 3 S 2 Oxygen evolution performance of @NF and its corresponding control samples, also based on the Ni 3 S 2 @NF, commercial RuO supported by nickel foam 2 (RuO 2 @NF) and clean nickel foam (NF) were used as control samples, and their performance is shown in Figure 3 As shown in Figure a, Ru-Ni 3 S 2 @NF also exhibits excellent oxygen evolution catalytic performance, and its oxygen evolution performance far exceeds that of Ni 3 S 2 @NF and RuO 2 @NF, which further explains Ru and Ni 3 S 2 The heterostructure formed between them can significantly improve the Ni 3 S 2 The oxygen evolution catalytic performance of Figure 3 As shown in Figure b, when the current density reaches 100 mA cm -2 , 200mA cm -2 and 400mAcm -2 Time Ru-Ni 3 S 2 @NF requires the lowest overpotential.

[0076] 3. Full electrolysis water performance test

[0077] (1) Based on the Ru-Ni prepared in this example 3 S 2 @NF exhibits excellent catalytic performance for both hydrogen and oxygen evolution. 3 S 2@NF as cathode and anode to assemble a two-electrode full water electrolysis device (Ru-Ni 3 S 2 @NF / / Ru-Ni 3 S 2 @NF), such as Figure 4 As shown in Figure a, RuO 2 The two-electrode system assembled with RuO@NF and Pt / C@NF was used as the control sample (RuO 2 @NF / / Pt / C@NF), such as Figure 4 The polarization curve of the full electrolysis of water in Figure b shows that Ru-Ni 3 S 2 The water electrolysis performance of the dual-electrode water electrolysis device assembled with @NF is much better than that of the commercial RuO 2 and Pt / C assembled dual electrode system.

[0078] (2) Based on Ru-Ni 3 S 2 @NF has excellent full water electrolysis performance and has been tested for stability. Figure 5 As shown in Figure a, at a current density of 50 mA cm -2 When the voltage was continuously operated for 28 h, there was no significant increase in the voltage, which indicated that the prepared Ru-Ni 3 S 2 @NF has excellent full water electrolysis stability. It was also tested for CV cycle stability, such as Figure 5 As shown in Figure b, the polarization curve did not change significantly before and after 4000 CV cycles, further indicating that the Ru-Ni prepared in this example 3 S 2 @NF has excellent stability in full water electrolysis.

[0079] Example 2

[0080] The difference between this embodiment and the first embodiment is that the solvent thermal reaction is carried out at 120°C for 5 hours.

[0081] Example 3

[0082] The only difference between this embodiment and the first embodiment is that the solvent thermal reaction is carried out at 180° C. for 5 hours.

[0083] Example 4

[0084] The difference between this embodiment and the first embodiment is that the solvent thermal reaction is carried out at 150° C. for 3 hours.

[0085] Example 5

[0086] The difference between this embodiment and the first embodiment is that the chemical etching reaction is carried out at 100° C. for 12 hours.

[0087] Example 6

[0088] The difference between this embodiment and the first embodiment is that the chemical etching reaction is carried out at 120° C. for 12 hours.

[0089] Example 7

[0090] The difference between this embodiment and the first embodiment is that the chemical etching reaction is carried out at 80° C. for 6 hours.

[0091] Example 8

[0092] The difference between this embodiment and the first embodiment is that the chemical etching reaction is carried out at 80° C. for 18 hours.

[0093] Example 9

[0094] The difference between this embodiment and the first embodiment is that: in this embodiment, 0.5 mg / mL of RuCl 3 Chemical etching reaction is carried out under the following conditions.

[0095] Example 10

[0096] The difference between this embodiment and the first embodiment is that: in this embodiment, 2 mg / mL of RuCl 3 Chemical etching reaction is carried out under the following conditions.

[0097] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A ruthenium nanocluster / nickel disulfide heterojunction composite material, characterized in that: The composite material uses nickel foam as a base material, a Ni3S2 nanosheet array is in-situ grown on the surface of the base material, and ruthenium nanoclusters are anchored on the surface of the Ni3S2 nanosheet array to form a heterojunction composite material.

2. The ruthenium nanocluster / nickel disulfide heterojunction composite material according to claim 1, characterized in that: The ruthenium nanocluster / nickel disulfide heterojunction composite material is a honeycomb structure.

3. The ruthenium nanocluster / nickel disulfide heterojunction composite material according to claim 1, characterized in that: The loading amount of the ruthenium nanocluster is less than or equal to 427.6 μg cm -2 .

4. A method for preparing the ruthenium nanocluster / nickel disulfide heterojunction composite material as claimed in claims 1 to 3, characterized in that: The following steps are involved: S1. Provide a nickel foam; S2, immersing the nickel foam in a mixed solvent, adding a nickel source and a sulfur source and mixing them, and performing a solvothermal reaction to obtain a Ni3S2 ultrathin nanosheet array supported by the nickel foam; S3, adding the Ni3S2 ultra-thin nanosheet array loaded with nickel foam obtained in step S2 into the ruthenium source solution, reacting at a constant temperature, and obtaining the ruthenium nanocluster / nickel disulfide heterojunction composite material.

5. The preparation method according to claim 4, characterized in that: In step S2, the nickel source is selected from one or more of Ni(NO3)2, NiSO4 and Ni(CH3COO)2; The concentration of the nickel source is 0.01-0.05 mmol; The mixed solvent includes ethanol and N,N-dimethylacetamide; The volume ratio of the ethanol to N,N-dimethylacetamide is (1:1)-(4:1).

6. The preparation method according to claim 4, characterized in that: In step S2, the molar ratio of the sulfur source to the nickel source is (1:1)-(3:1); The sulfur source is selected from one or more of thioacetamide, thiourea, L-cysteine ​​and sulfur powder; The conditions of the solvent thermal reaction are: reaction temperature 100-180° C., reaction time 3-8 h.

7. The preparation method according to claim 4, characterized in that: In step S3, the ruthenium source in the ruthenium source solution is selected from RuCl3 and / or terpyridine ruthenium chloride hexahydrate; The concentration of the ruthenium source is 0.2-4 mg / mL ; The solvent of the ruthenium source is selected from ethanol and / or deionized water; The temperature of the isothermal reaction is 60-100° C., and the isothermal time is 8-16 hours.

8. An oxygen evolution electrode, characterized in that: The invention comprises the ruthenium nanocluster / nickel disulfide heterojunction composite material according to any one of claims 1 to 3.

9. A hydrogen evolution electrode, characterized in that The invention comprises the ruthenium nanocluster / nickel disulfide heterojunction composite material according to any one of claims 1 to 3.

10. An electrochemical device for water electrolysis reaction, characterized in that: It comprises the oxygen evolution electrode as claimed in claim 8 or the hydrogen evolution electrode as claimed in claim 9.

Citation Information

Cited By

  • Electrocatalyst with RuFe nanoparticles cooperating with Ni3S2 and MXene heterojunction and application of electrocatalyst

    CN119685844A

  • Electrocatalyst of RuFe nanoparticles synergized with Ni3S2 and MXene heterojunction and application thereof

    CN119685844B